Pedagogical Management: The Key to Enhancing Academic Performance and Educational Quality - Pablo-Huamani, Rebeca (2024)
The purpose of this research is to determine the significance of pedagogical management (PM) in the teaching practice of instructors and the relationship between it and students’ academic achievement. 23 scholarly papers were reviewed bibliographically in order to perform the investigation. The findings show a strong correlation between high-quality instruction and efficient pedagogical administration. It highlights that the instructor is the change agent in this process and that the student’s educational transformation depends on their own personal growth. The conclusion highlights the significance of PM as a crucial component in obtaining quality education and emphasizes how the quality of the teaching process reflects on the quality of education. The present study holds significant value for the educational sector because it emphasizes the necessity of concentrating improvement efforts on teacher preparation and classroom management skills. These have been identified as critical points, particularly in higher education, where a pedagogical management crisis has been identified.